A MECHANICAL INTERPRETATION OF THE ELECTRICAL ACTIVITY OF THE WORKING MUSCLES AS A FUNCTION OF PREDICTING THE PERFORMANCE OF THE CRUCIATE FULCRUM SKILL ON THE THROAT APPARATUS IN ARTISTIC GYMNASTICS FOR MEN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The mechanical explanation of the bioelectrical activity of the elements of the cruciate support skill on the throat apparatus in men's gymnastics has not been widely understood in scientific research to date. Given the increasing challenge of implementing experimental protocols and collecting data from multiple individuals, it is necessary to develop strategies that allow for safe, valid, and reproducible methodology. The research problem can be summarized with the following question: Is it possible to obtain numerical values through mechanical analysis of the muscles working during the main stage of performance (balance) through which this can determine the most important strengths and weaknesses that accompany performance and how to benefit from it and develop solutions to weak points and evaluate and benefit from them? Strengths and their relationship to the force produced by the major muscles during the major phase in terms of electrical activity, bearing in mind that gymnastics offers almost limitless possibilities for studying human movement. Researchers should focus on the type of item, degree of difficulty, and key characteristics. The relationship between the device and the specifics of the device specifications and safety conditions. The axis of the joint represents the fulcrum of the crane. The force of muscle contraction represents force and body weight represents resistance. The research aimed to identify the electrical activity of the working muscles during the main stage of performing the cruciate anchor skill on the throat apparatus in gymnastics for men. The researcher hypothesized that there would be a positive effect of the mechanical interpretation of the electrical activity of the working muscles as a function of predicting the performance of the anchor skill. The cruciate on the throat apparatus in artistic gymnastics for men. The research aimed to identify the effect of mechanical interpretation of the electrical activity of the working muscles as a function of predicting the performance of the skill of the cruciate fulcrum on the throat apparatus in artistic gymnastics for men. The researcher used the descriptive approach as it is the most appropriate method for the nature of the research problem. The researcher chose a combined Originally, they were players from the national teams of the Middle Euphrates governorates. The research sample was chosen intentionally, consisting of 10 players. The player made one attempt at the skill study, and the primary muscles on the right side of the player were measured on the throat device. It is considered a model of strength skills in men’s gymnastics, and one must hold still for at least two seconds in competition. As an example of approximating the shoulder joints and performing skills that require the use of the same muscles responsible for adducting the shoulder joints, the skill of cruciate support on the throat apparatus in gymnastics for men was chosen. Five main working muscles were selected for this skill and to identify the percentage of their contribution during the performance of the study skill as well. The hypothesis was achieved by constructing a predictive equation that can be used in evaluating performance. The results indicated that the teres major muscle came in first place, the teres major muscle came in second place, and the pectoralis major muscle came in third place, and the latissimus dorsi muscle came in fourth place, in percentage. Then the triceps brachii (long head) came in last place in percentage. Then the triceps brachii (long head) came in last place in percentage. The mechanical analysis of the working muscle points for skill performance and achieving the principle of balance is considered one of the important points that have not been given a large share by researchers due to the difficulty of providing modern equipment and modern laboratories and the high financial cost through the process of linking the sciences to find out the mechanism and nature of those sciences and the nature of values. The digital one gives us accurate numerical values for the nature of the work of all the muscles involved in performance and the percentage of each one of them, in addition to the nature of the mechanical contraction associated with it.